Emergency Medicine Residency Selection Criteria: An Update and Comparison. Issue 2 (22nd March 2018) - Negaard, Matthew; Assimacopoulos, Evangelia; Harland, Karisa; Van Heukelom, Jon
Abstract: Objective: The primary objective was to describe emergency medicine (EM) residency selection criteria. Methods: A survey was sent to the Council of Emergency Medicine Residency Directors listserv. Respondents were asked to rank order the various components of the application on a Likert scale from 1 (minimally important) to 10 (highly important). The mean ranking and standard deviation for each of the components were calculated. The survey sought to determine characteristics associated with offering an applicant an invitation to interview and subsequent ranking. Percentages with defined minimum requirements were calculated. Comparisons across residency length and location were completed with a Pearson chi‐square test for categorical variables and Student's t‐test for continuous variables. Results: A total of 120 surveys were completed. The highest ranked components included away/visiting institution departmental standardized letter of evaluation (SLOE) (mean ± SD = 8.80 ± 1.25), residency interview (mean ± SD = 8.74 ± 1.28), home institution departmental SLOE (mean ± SD = 8.61 ± 1.18), away/visiting institution EM rotation grade (mean ± SD = 8.29 ± 1.43), and home institution EM rotation grade (mean ± SD = 8.07 ± 1.42). The most consistently ranked items included home institution departmental SLOE (SD = 1.18), away/visiting institution departmental SLOE (1.25), and residency interview (1.28). Characteristics associated with offering an interview to an applicant included only 10% of responses indicating a United States Medical Licensing Examination Step 1 score of 220 was needed. At least one SLOE was required in 80% of responses. Program location was related to the number of SLOEs required (p = 0.03). Length of residency and program location differed significantly in how a residency ranked components when considering an applicant (p < 0.05). Conclusion: Emergency medicine programs put high value in departmental SLOEs, the interview, and EM rotation grades when selecting potential residents. Higher value is placed on SLOEs and grades from away/visiting institutions compared with students' home institutions.